2005
DOI: 10.1002/cncr.21439
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pathologic complete response after preoperative chemoradiotherapy in carcinoma of the esophagus and outcome after pathologic complete response

Abstract: Objective The collagen VI muscular dystrophies, Bethlem myopathy and Ullrich congenital muscular dystrophy, form a continuum of clinical phenotypes. Glycine mutations in the triple helix have been identified in both Bethlem and Ullrich congenital muscular dystrophy, but it is not known why they cause these different phenotypes. Methods We studied eight new patients who presented with a spectrum of clinical severity, screened the three collagen VI messenger RNA for mutations, and examined collagen VI biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
6
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 54 publications
3
67
6
3
Order By: Relevance
“…Fifty-seven patients started the concurrent phase of the treatment: 49 (83%) of them received the whole radiotherapy dose. Unplanned interruptions of more than 2 days occurred in 14 patients as a result of toxicity; 8 patients discontinued radiotherapy due to esophagitis and diarrhea after a median of 40 Gy (range [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Table 2 lists the whole incidence of toxicity during chemo-radiotherapy.…”
Section: Chemo-radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-seven patients started the concurrent phase of the treatment: 49 (83%) of them received the whole radiotherapy dose. Unplanned interruptions of more than 2 days occurred in 14 patients as a result of toxicity; 8 patients discontinued radiotherapy due to esophagitis and diarrhea after a median of 40 Gy (range [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Table 2 lists the whole incidence of toxicity during chemo-radiotherapy.…”
Section: Chemo-radiotherapymentioning
confidence: 99%
“…In advanced (T3 and T4) esophageal cancer, a complete clearance of tumor cells is more diYcult to obtain [34]. A weekly schedule, which should optimize the inhibition of sub-lethal radiation-induced DNA damage repair [4,11], might increase the pathological complete response (pCR) rate through greater tumor shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, clinical parameters do not predict outcome before the start of therapy. [15][16][17][18] However, the initial results and subsequent changes in positron emission tomography (PET) show promise. [19][20][21][22][23][24][25] Many investigators have demonstrated that decrease in metabolic activity as measured by the standardized uptake value (SUV) on PET/computed tomography (CT) as a result of therapy is of prognostic value.…”
mentioning
confidence: 99%
“…In patients with oesophageal adenocarcinoma long-term survival is strongly correlated with the achievement of pathological complete response (pCR) to neoadjuvant chemoradiotherapy (Walsh et al, 1996;Geh et al, 2001;Urba et al, 2001;Berger et al, 2005;Burmeister et al, 2005;Rohatgi et al, 2005). However, in the US Intergroup and OEO2 trials of preoperative chemotherapy, the pCR rates were only 2 and 4%, respectively (Kelsen et al, 1998;MRC, 2002).…”
mentioning
confidence: 99%